2019
DOI: 10.1002/hed.25689
|View full text |Cite|
|
Sign up to set email alerts
|

Aurora kinase A induces chemotherapy resistance through revival of dormant cells in laryngeal squamous cell carcinoma

Abstract: Background: Chemotherapy resistance was an important tumor metastasis mechanism. Methods: Cell Counting Kit-8 assay and plate colony formation assay were applied to examine the proliferation of laryngeal squamous cell carcinoma (LSCC). Immunofluorescent staining and Western blotting were carried out to show the expression of related proteins. Wound healing, migration, and invasion assays were used to examine the mobility, migration, and invasion of LSCC. Results: Downregulated Aurora kinase A (AURKA) increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…AURKA is frequently ampli ed and/or overexpressed in GI malignancies (including esophageal, gastric, and colorectal and head and neck cancers) [16][17][18][19] . Our previous research found Aurora kinase A (AURKA) revives dormant LSCC to promote LSCC metastasis 3,5 . Therefore, illustrating speci c molecular mechanism of AURKA revives dormant LSCC to promote LSCC metastasis was of great concern.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AURKA is frequently ampli ed and/or overexpressed in GI malignancies (including esophageal, gastric, and colorectal and head and neck cancers) [16][17][18][19] . Our previous research found Aurora kinase A (AURKA) revives dormant LSCC to promote LSCC metastasis 3,5 . Therefore, illustrating speci c molecular mechanism of AURKA revives dormant LSCC to promote LSCC metastasis was of great concern.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous research found Aurora kinase A (AURKA) revives dormant LSCC to promote metastasis 3,5 . Therefore, illustrating speci c molecular mechanism of AURKA revives dormant LSCC to promote metastasis was of great concern.…”
Section: Introductionmentioning
confidence: 99%
“…AURKA is frequently ampli ed and/or overexpressed in GI malignancies (including esophageal, gastric, and colorectal and head and neck cancers) [16][17][18][19] . Our previous research found Aurora kinase A(AURKA) revives dormant LSCC to promote LSCC metastasis 3,5 .Therefore, illustrating speci c molecular mechanism of AURKA revives dormant LSCC to promote LSCC metastasiswas of great concern. The key moleculesmaybe capable to potential prognostic value and potential targets for clinical LSCC treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous research found Aurora kinase A(AURKA) revives dormant LSCC to promote metastasis 3,5 .Therefore, illustrating speci c molecular mechanism of AURKA revives dormant LSCC to promote metastasiswasof great concern. The key moleculesmaybe capable to potential prognostic value and potential targets for clinical LSCC treatment.…”
Section: Introductionmentioning
confidence: 99%